PENGARUH GAYA BELAJAR EXPERIENTIAL LEARNING DALAM PENINGKATAN PRESTASI AKADEMIK DAN PENERAPANNYA DALAM PEMBELAJARAN - Sugiyanto Sugiyanto (Paradigma, 2012)
Teachers in the learning process, should pay attention tothe characteristics of their students. A wide range of studentcharacteristics, both internally and externally. One of thecharacteristics of students in learning that need to be considered inteacher learning and affect the effectiveness of teaching and learningis the learning styles of the students.Experiential Learning not only provide insight into the conceptsof knowledge alone. However, it also gives a real experience that willbuild skills through real assignments. Experienced learning theory isformed through a process of suppression. Suppression processincludes concrete experience, observe /reflect on concreteexperiences, abstract concepts and generalizations formatting, to testimplications of concepts in new situations. The four processes formthe four types of learning styles are: konverger, akomodator,diverger, and assimilator.Teachers in teaching has its own learning style as well as thetypes of students have learning styles but it does not mean the qualityof teaching by itself will increase. Learning style is closely related toan individual's personal history influenced by education anddevelopment. This is because the factors that affect academicachievement itself. Therefore, in the learning process teachers needto pay attention to the types of learning styles of the students as wellas teachers also have their own learning style.Keywords : learning styles, experiential learning, academicachievement, learning